To solve the equation 4 - t = 3(t - 1) - 5, we can start by simplifying both sides of the equation.
4 - t = 3(t - 1) - 5
Let's distribute the 3 on the right side of the equation.
4 - t = 3t - 3 - 5
Next, combine like terms.
4 - t = 3t - 8
Now, we can isolate the variable t by moving all terms involving t to one side of the equation.
-t - 3t = -8 - 4
Combine like terms.
-4t = -12
To isolate t, divide both sides of the equation by -4.
t = -12 / -4
Simplify the fraction.
t = 3
Therefore, the solution to the equation 4 - t = 3(t - 1) - 5 is t = 3.
solve the equation 4-t=3(t-1)-5
7 answers
8x - 2(x - 1) = 2(3x - 1)
To solve the equation 8x - 2(x - 1) = 2(3x - 1), we can start by simplifying both sides of the equation.
8x - 2(x - 1) = 2(3x - 1)
Let's distribute the 2 on both sides of the equation.
8x - 2x + 2 = 6x - 2
Combine like terms.
6x + 2 = 6x - 2
Next, subtract 6x from both sides of the equation.
6x - 6x + 2 = 6x - 6x - 2
Simplify.
2 = -2
However, this last equation, 2 = -2, is not true.
Therefore, there is no solution to the equation 8x - 2(x - 1) = 2(3x - 1).
8x - 2(x - 1) = 2(3x - 1)
Let's distribute the 2 on both sides of the equation.
8x - 2x + 2 = 6x - 2
Combine like terms.
6x + 2 = 6x - 2
Next, subtract 6x from both sides of the equation.
6x - 6x + 2 = 6x - 6x - 2
Simplify.
2 = -2
However, this last equation, 2 = -2, is not true.
Therefore, there is no solution to the equation 8x - 2(x - 1) = 2(3x - 1).
3(c-2) = 2(c-6)
To solve the equation 3(c-2) = 2(c-6), we can start by simplifying both sides of the equation.
3(c-2) = 2(c-6)
Let's distribute the 3 on the left side of the equation and the 2 on the right side of the equation.
3c - 6 = 2c - 12
Next, subtract 2c from both sides of the equation.
3c - 2c - 6 = 2c - 2c - 12
Simplify.
c - 6 = -12
Now, add 6 to both sides of the equation.
c - 6 + 6 = -12 + 6
Simplify.
c = -6
Therefore, the solution to the equation 3(c-2) = 2(c-6) is c = -6.
3(c-2) = 2(c-6)
Let's distribute the 3 on the left side of the equation and the 2 on the right side of the equation.
3c - 6 = 2c - 12
Next, subtract 2c from both sides of the equation.
3c - 2c - 6 = 2c - 2c - 12
Simplify.
c - 6 = -12
Now, add 6 to both sides of the equation.
c - 6 + 6 = -12 + 6
Simplify.
c = -6
Therefore, the solution to the equation 3(c-2) = 2(c-6) is c = -6.
0.5(m+4)=3(m-1)
To solve the equation 0.5(m+4) = 3(m-1), we can start by simplifying both sides of the equation.
0.5(m+4) = 3(m-1)
Let's distribute the 0.5 on the left side of the equation and the 3 on the right side of the equation.
0.5m + 2 = 3m - 3
Next, subtract 0.5m from both sides of the equation.
0.5m - 0.5m + 2 = 3m - 0.5m - 3
Simplify.
2 = 2.5m - 3
Now, add 3 to both sides of the equation.
2 + 3 = 2.5m - 3 + 3
Simplify.
5 = 2.5m
Next, divide both sides of the equation by 2.5 to isolate m.
5/2.5 = (2.5m)/2.5
Simplify.
2 = m
Therefore, the solution to the equation 0.5(m+4) = 3(m-1) is m = 2.
0.5(m+4) = 3(m-1)
Let's distribute the 0.5 on the left side of the equation and the 3 on the right side of the equation.
0.5m + 2 = 3m - 3
Next, subtract 0.5m from both sides of the equation.
0.5m - 0.5m + 2 = 3m - 0.5m - 3
Simplify.
2 = 2.5m - 3
Now, add 3 to both sides of the equation.
2 + 3 = 2.5m - 3 + 3
Simplify.
5 = 2.5m
Next, divide both sides of the equation by 2.5 to isolate m.
5/2.5 = (2.5m)/2.5
Simplify.
2 = m
Therefore, the solution to the equation 0.5(m+4) = 3(m-1) is m = 2.